NUZULUL QURAN SEBAGAI MOMENTUM REVITALISASI MORAL SOSIAL UMAT - Nazzril Maulana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze how the commemoration of Nuzulul Quran can serve as a moment for revitalizing the social morality of Muslim communities. The revelation of the Qur’an carries not only theological significance but also moral and social messages that are relevant to shaping the character of modern society. Using a qualitative approach based on literature review and discourse analysis, this research examines Qur’anic verses, classical and contemporary tafsir, as well as the practices of Nuzulul Quran commemoration in Indonesia. The findings reveal that Qur’anic values such as honesty, justice, social empathy, and moderation are essential messages of the first revelation. Nuzulul Quran can serve as a strategic moment to internalize these values within social life. This study highlights the importance of moral transformation grounded in Qur’anic teachings as a foundation for a civilized society.